Does nutritional status influence early child development? Evidance from infants in Bantul, Yogyakarta, Indonesia - Putri, Adelia Kholila; Ayuningrum, Lia Dian; Aryani, Farida; Arifin, Siti Roshaidai Mohd (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
ABSTRAKLatar Belakang: Perkembangan anak usia 1-24 bulan sangat dipengaruhi oleh status gizi. Kekurangan gizi dapat menghambat pertumbuhan fisik, kognitif, serta meningkatkan risiko stunting. Data WHO pada tahun 2024 mencatat 23,2% anak di bawah 5 tahun mengalami stunting. Sementara itu, laporan Survei Status Gizi Indonesia menunjukkan prevalensi 19,8% pada tahun 2024. Dinas Kesehatan Bantul mencatat 7,01% balita mengalami stunting pada Juni 2024, Puskesmas Srandakan tercatat prevalensi tertinggi yaitu 13,94%.Tujuan: Mengetahui hubungan status gizi terhadap perkembangan anak usia 1-24 bulan.Metode: Penelitian survei analitik dengan desain cross-sectional ini dilakukan di posyandu wilayah kerja Puskesmas Srandakan pada 14 Meiâ€“11 Juni 2025. Sebanyak 104 anak usia 1â€“24 bulan dipilih melalui cluster random sampling. Status gizi diukur dengan antropometri dan perkembangan anak menggunakan KPSP. Analisis data menggunakan uji korelasi Spearman Rank.Hasil: Mayoritas anak memiliki status gizi baik (83,7%) dan perkembangan yang sesuai (68,3%). Analisis statistik menggunakan uji Spearman Rank menunjukkan tidak terdapat hubungan yang signifikan antara status gizi dan perkembangan anak dengan nilai p = 0,976.Kesimpulan: Penelitian ini menunjukkan tidak terdapat hubungan signifikan antara status gizi dan perkembangan anak usia 1â€“24 bulan di wilayah kerja Puskesmas Srandakan, Bantul. Meskipun sebagian besar anak bergizi normal, variasi perkembangan tetap ditemukan pada semua kelompok gizi. Temuan ini mengindikasikan bahwa faktor lainâ€”seperti stimulasi, praktik pengasuhan, dan lingkungan psikososialâ€”juga berperan penting. Oleh karena itu, peningkatan perkembangan anak perlu mengintegrasikan intervensi gizi dengan edukasi pengasuhan dan stimulasi yang lebih terarah. KATA KUNCI: baduta; perkembangan anak; status gizi; stunting                                                                                                                                                                                    ABSTRACTBackground: The development of children aged 1-24 months is significantly influenced by nutritional status. Malnutrition can inhibit physical and cognitive growth, and increase the risk of stunting. WHO data in 2024 recorded 23.2% of children under 5 years old experiencing stunting. Meanwhile, the Indonesian Nutritional Status Survey report showed a prevalence of 19.8% in 2024. The Bantul Health Office recorded 7.01% of toddlers experiencing stunting in June 2024, while the Srandakan Community Health Center recorded the highest prevalence at 13.94%.Objective: To determine the relationship between nutritional status and the development of children aged 1-24 months.Method: This analytical survey with a cross-sectional design was conducted at the integrated health service post (posyandu) in the working area of the Srandakan Community Health Center. Total of 104 children aged 1-24 months were selected through cluster random sampling. Nutritional status was measured using anthropometry and child development using the KPSP. Data analysis used the Spearman Rank correlation test.Results: The majority of children had good nutritional status (83.7%) and appropriate development (68.3%). Statistical analysis using the Spearman Rank test showed no significant relationship between nutritional status and child development with a p-value of 0.976.Conclusion: This study shows no significant relationship between nutritional status and development in children aged 1â€“24 months in the Srandakan Community Health Center (Puskesmas) area, Bantul. Although most children had normal nutrition, developmental variations were found across all nutrition groups. These findings indicate that other factorsâ€”such as stimulation, parenting practices, and the psychosocial environmentâ€”also play a significant role. Therefore, improving child development requires integrating nutritional interventions with more targeted parenting education and stimulation. KEYWORD: child development; infant; nutritional status; stunting  Article submitted on August 05, 2025; Articles revised on September 11, 2025; Articles received on November 20, 2025; Articles available online on November 28, 2025